The effects of protective factors and adverse childhood experiences on behavioral health services use: Findings from a population-based sample. (9th August 2018) - Larkin, Heather; Lee, Eunju; Esaki, Nina; DeMasi, Mary; Trifoso, Shawn; Briar-Lawson, Katharine; Dean, Erica; Weldon, Patricia; Park, Jihyun; Bowen, Lara; Benson, Deborah; Cortese, Anthony; et al.
ABSTRACT: Adverse childhood experiences (ACEs) are linked to later life health problems such as behavioral health (BH) service use but less is known about how to counter this association. Using a population based sample of 807 adults, we examined the effects of protective factors in countering this association. ACEs were associated with increased BH service use while protective factors were associated with decreased BH service use. However, no significant interaction effect was found. Research is needed to develop a better measure of protective factors. Social workers need to be aware of ACE prevalence among clients and can foster protective factors.